"Honor List" and "Shame Roll": Quasi-Experimental Evidence of the Effect of Performance Feedback under Political Control. (18th February 2022) - Wei, Wenchi; Wang, Chengwei; Zhai, Wenkang; Li, Wenzhao
Abstract: This article examines how the use of an "honor list" and "shame roll" as a means of performance feedback can influence governments' future performance improvement, focusing on a prominent performance management reform implemented in Chinese local governments. We draw upon classic behavioral theories of organizations to propose testable hypotheses. The empirical analyses use 3, 300 observations based on the 333 grassroots governments of the capital city of China as the unit of analysis. Regression discontinuity design estimations show that entering the honor list reduces governments' performance improvement in the next period, while entering the shame roll helps governments improve their performance. Moreover, the level of performance improvement is higher at the cutoff for both the honor list and shame roll if governments rely more on the higher authority's fiscal resources. This study advances a more nuanced understanding of the performance feedback effect under political control and a rigid administrative hierarchy.